Data Governance as the Enabler of the Data Economy - Barbara Engels (Intereconomics, 2019)
Data governance beyond compliance sees data as a strategicasset. It breaks the silos of data present at differentstages of the business process and in different businessunits while also making high-quality data available to allbusiness processes and all business units according totheir current and future needs and requirements.
Keywords: 330